Pelvic rotation dynamics of accuracy enhanced, submaximal effort instep soccer kicking - Inoue, K.; Nunome, H. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to clarify the kinetic aspects of the pelvic rotation in accuracy enhanced, submaximal effort soccer instep kicking. Fifteen male soccer players conducted instep kicking in a maximal (MAX) effort and a submaximal (SUB) effort with an emphasis on accuracy. Kicking motions were recorded by a motion capture system with a force platform at 500 Hz. The counter-clockwise pelvic rotation decreased significantly in SUB. Also, the interaction torque on the support leg hip joint decreased significantly in SUB. A previous study reported that the interaction torque was the primary factor in producing pelvic rotation. Thus, controlled pelvic rotation seen in SUB is most likely due to a reduced interaction torque acting on the support leg hip joint. It can be considered that to restrain pelvic rotation is a strategy to slow down the foot swing velocity in accuracy enhanced, submaximal effort instep kicking.